Structural relationship between emotional and social support for young adult carers towards intergenerational care of the multi-ethnic elderly - Nurul Hudani Md. Nawi; Puteri Hayati Megat Ahmad; Mohd Dahlan A. Malek; Getrude Cosmas; Habibie Ibrahim; Peter Voo Su Kiong; Norazah Mohd Suki (Emerald Group Publishing Ltd., 2017)
Purpose: The purpose of this paper is to examine the structural relationship between the emotional and social support provided for individuals with caring responsibilities for elderly relatives, and the quality of care actually delivered. In addition, the moderating role of gender is explored. Design/methodology/approach: A quantitative research design was utilised in which 200 usable questionnaires were collected from 250 respondents comprised of young adults who adopt a caregiving roles in respect of elderly parents or other close elderly relatives. The structural equation modelling (SEM) technique was selected for data analysis, and the Analysis of moment structure software version 21 was used. Findings: The SEM results revealed that emotional support for caregivers was the most important predictor affecting the intergenerational care of multi-ethnic elderly people. Additionally, a moderation analysis revealed that the relative influence in this connection was more pronounced among female caregivers. An increase in the emotional support received by the recipient was found to enhance the level of the relationship, and to result in closer intergenerational ties in the care of the multi-ethnic elderly. Furthermore, the receipt of social support positively influences the judgement of an individual, and expands that person’s social network, which can subsequently have a favourable impact on the way in which one fulfils their caring role. The significant effect of social support provided for intergenerational caregivers in the context of the multi-ethnic elderly was higher in the group of male caregivers than in the group of female caregivers. Practical implications: This study sends a strong message to policy-makers in developing countries about the need to consider within their National Policy for the Elderly, improvements in the national action plan for a holistic and integrated approach to ensure the well-being of caregivers and the elderly. Originality/value: The results of the study help young adults to understand the importance of emotional and social support in boosting their relationships with parents and families and motivating intergenerational efforts in the care of the multi-ethnic elderly. Harmony within families is an important ideal in any circumstance, but in the scenario of ageing family members it may be even more essential to try to achieve it.